The role of viral and host factors in alveolar fluid clearance during Influenza A virus-induced lung injury - Becker, Christin; Justus Liebig University Giessen (My University, 2015)
Influenza A viruses (IAV) cause primary viral pneumonia resulting in acute respiratory distress syndrome (ARDS) associated with severe alveolar edema formation. As impairment of edema resolution in ARDS patients is correlated with high mortality, this study investigated metabolism and function of Na,K-ATPase, a major regulator of fluid homeostasis, to define mechanisms affecting alveolar fluid clearance (AFC) in IAVinfection. In vivo IAV infection of wildtype (wt) mice resulted in reduced AFC, edema formation and hypoxia that occurred in parallel with a decrease in total and plasma membrane expressed Na,K-ATPase alpha1 subunit (NKAalpha1). NKAalpha1 was primarily decreased in non-infected cells in a monoculture of alveolar epithelial cells (AEC) and in presence of co-cultured, infected macrophages. We found paracrine signaling of type I interferons (IFN) and the macrophage released, IFN-dependent cytokine TRAIL (TNF-related apoptosis inducing ligand) to be sufficient to decrease NKAalpha1 in a CaMKKbeta- and AMPK-dependent way. Blockade of this pathway using specific chemical inhibitors, adenoviral overexpression or siRNA approaches restored NKAalpha1 levels as well as vectorial water transport in ex vivo infected AEC. Additionally, trail-/- or ifnar-/- mice, mice transduced with a dominant-negative form of AMPK or ccr2-/- mice lacking pulmonary macrophage recruitment showed improved NKAalpha1 levels and AFC after IAV infection. In parallel, inhibition of Na,K-ATPase channel activity by ouabain reduced the amount of IAV infected cells, implying a role for Na,KATPase in the IAV replication cycle. IAV infection or transfection of the viral M segment led to a mistargeting of NKAalpha1 from the basolateral to the apical cell surface in infected AEC, associated with a close interaction between the viral M2 protein and the NKAalpha1, likely resulting in impaired or even reverted fluid clearance in the infected fraction of AEC. Together, this work demonstrates that AFC is inhibited after IAV infection both in infected cells by M2-mediated mistargeting and in non-infected neighboring cells by paracrine IFN/TRAIL/DR5 signaling resulting in AMPK-mediated decrease of plasma membrane NKAalpha1. Targeting these pathways may be a novel therapeutic strategy to improve AFC, oxygenation and finally outcome in patients with IAV-induced ARDS.
Keywords: ddc:610